2017
DOI: 10.1002/chem.201701480
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Average Thermoelectric Figure of Merit, Low Lattice Thermal Conductivity and Enhanced Microhardness in Nanostructured (GeTe)x(AgSbSe2)100−x

Abstract: Waste heat sources are generally diffused and provide a range of temperatures rather than a particular temperature. Thus, thermoelectric waste heat to electricity conversion requires a high average thermoelectric figure of merit (ZT ) of materials over the entire working temperature along with a high peak thermoelectric figure of merit (ZT ). Herein an ultrahigh ZT of 1.4 for (GeTe) (AgSbSe ) [TAGSSe-80, T=tellurium, A=antimony, G=germanium, S=silver, Se=selenium] is reported in the temperature range of 300-70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 49 publications
2
84
0
1
Order By: Relevance
“…The intrinsic lattice thermal conductivity of AgSbTe 2 and GeTe is about 0.7 and 2.6 W mK −1 , respectively. [ 33,34 ] Intuitively, it might be normal to expect a lower lattice thermal conductivity with increasing the content of AgSbTe 2 in the TAGS system. However, the κ l value at room temperature for TAGS‐75, TAGS‐80, and TAGS‐85 was reported to be 0.8, 0.6, and 0.7 W mK −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intrinsic lattice thermal conductivity of AgSbTe 2 and GeTe is about 0.7 and 2.6 W mK −1 , respectively. [ 33,34 ] Intuitively, it might be normal to expect a lower lattice thermal conductivity with increasing the content of AgSbTe 2 in the TAGS system. However, the κ l value at room temperature for TAGS‐75, TAGS‐80, and TAGS‐85 was reported to be 0.8, 0.6, and 0.7 W mK −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to AgSbTe 2 , AgSbSe 2 has also an intrinsically low lattice thermal conductivity due to the large anharmonicity. Samanta et al [ 34 ] reported that the lattice thermal conductivity is minimized in the compound with 20 at% AgSbSe 2 . Adding more AgSbSe 2 oppositely increases the lattice thermal conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Histogram of Vickers microhardness, H v values of GeTe‐based thermoelectric materials and typical metal chalcogenides. [ 77,96,153–157 ] …”
Section: Heat Transport Performance Reductionmentioning
confidence: 99%
“…[ 77 ] Moreover, H v value of (GeTe) 80 (AgSbSe 2 ) 20 is effectively improved to 209 Kgf mm −2 through suppressing the expansion of nano‐ and microcracks with AgSbSe 2 nanoprecipitates. [ 153 ] Comparing with other high‐performance chalcogenide thermoelectric materials, GeTe exhibits relatively higher H v values, indicating a better mechanical stability.…”
Section: Thermoelectric Devices and Modulesmentioning
confidence: 99%
“…[30,37,38] Forr hombohedral GeSe,t he band structure is quite similar to that of rhombohedral GeTe, ag ood thermoelectric material (TAGS). [25][26][27][28][29] Rhombohedral GeTee xhibits high carrier concentration due to intrinsic Ge vacancies. [39][40][41] Theformation energy of Ge vacancies in rhombohedral GeTe is low meaning Ge vacancies can form easily.…”
Section: Angewandte Chemiementioning
confidence: 99%